Ambroxol confers neuroprotection against scopolamine-induced Alzheimer’s-like pathology by modulating oxidative stress, neuroinflammation, and cognitive deficits via Nrf-2/JNK/GSK-3β signaling pathways - Waqas Ahmad; Kyonghwan Choe; Kyonghwan Choe; Riaz Ahmad; Tae Ju Park; Myeong Ok Kim; Myeong Ok Kim (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is the most common and costly chronic progressive neurodegenerative disorder, with the highest impact on public health worldwide. Pathological hallmarks of AD include progressive cognitive decline and memory impairment, dominantly mediated by oxidative neurodegeneration. Oxidative stress is commonly recognized as a key factor in the pathophysiological progression of AD. Despite significant advancements, a definitive and effective therapeutic intervention for AD remains elusive. In this study, we investigate the neuroprotective potential of ambroxol (Amb), known for its potent anti-inflammatory and antioxidant properties. Given ambroxol’s potential neuroprotective effects, we explore the underlying molecular mechanisms, explicitly examining its role in attenuating scopolamine-induced oxidative stress-mediated activation of the c-Jun N-terminal kinase (JNK) pathway, as well as its modulation of Akt and glycogen synthase kinase-3 beta (GSK-3β) signaling, which is a key contributor to neuroinflammation, synaptic dysfunction and neurodegeneration. AD pathology is induced by scopolamine administration, leading to excessive lipid peroxidation (LPO) and reactive oxygen species (ROS) generation, which leads to a decline in critical antioxidant proteins, including nuclear factor erythroid 2-related factor 2 (Nrf-2) and heme oxygenase-1 (HO-1). However, ambroxol treatment effectively attenuated oxidative stress by reducing the production of reactive oxidative species while restoring the expression of key antioxidant proteins. Similarly, ambroxol attenuated oxidative stress-induced JNK activation and modulated Akt and GSK-3β alterations. Immunofluorescence and western blot analyses revealed that ambroxol attenuated reactive gliosis by suppressing the expression of GFAP and Iba-1, alongside the downregulation of key pro-inflammatory mediators, such as IL-1β, TNF-α, and phosphorylated NF-κB (p-p65). Scopolamine also compromised synaptic integrity and induced deficits in memory formation and spatial learning. In contrast, ambroxol promoted synaptic integrity by upregulating the expression of SNAP-23 and PSD-95, thereby ameliorating scopolamine-induced impairments in spatial learning and memory.